1986
DOI: 10.1302/0301-620x.68b3.3733813
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental replacement and high tibial osteotomy for osteoarthritis of the knee. A comparative study after 5-10 years' follow-up

Abstract: We have made a restrospective comparison between the results of 49 high tibial osteotomies and 42 unicompartmental replacement arthroplasties performed for the treatment of osteoarthritis of the knee, assessed S to 10 years after operation. The type of operation depended on the policy of the consultant responsible for treatment but analysis of the pre-operative findings showed that the two groups were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0
4

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(84 citation statements)
references
References 0 publications
1
79
0
4
Order By: Relevance
“…Some series have reported (Aglietti et al 1983, Rudan and Smurda 1991, Yasuda et al 1992) good early results in up to 88% of cases following HTO, which deteriorated to 64% or less at 10 years. Broughton et al (1986) found only 43% good or excellent results following HTO, compared to 76% with UKA at 5-10 years after operation in a similar group of patients. Weale and Newman (1 994) further reviewed patients from the same group at 12-17 years after operation and concluded that the superior results of unicompartmental arthroplasty compared to the HTO were maintained after a prolonged follow-up period.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Some series have reported (Aglietti et al 1983, Rudan and Smurda 1991, Yasuda et al 1992) good early results in up to 88% of cases following HTO, which deteriorated to 64% or less at 10 years. Broughton et al (1986) found only 43% good or excellent results following HTO, compared to 76% with UKA at 5-10 years after operation in a similar group of patients. Weale and Newman (1 994) further reviewed patients from the same group at 12-17 years after operation and concluded that the superior results of unicompartmental arthroplasty compared to the HTO were maintained after a prolonged follow-up period.…”
Section: Discussionmentioning
confidence: 80%
“…All arthroplasties were followed prospectively before operation and then 2, 5, 8, 10, 12 and 15 years after operation. The assessment was based on a modified Bristol Knee Scoring system (Broughton et al 1986), which included pain score. Patients were asked to grade pain in the knee as none, mild, moderate or severe at rest and also while weight bearing.…”
Section: Methodsmentioning
confidence: 99%
“…Broughton et al [11] retrospectively reviewed at five to ten years follow-up 49 lateral closing wedge HTO and 42 UKA. They reported 76% of good results with UKA and 43% with HTO.…”
Section: Type Of Fixationmentioning
confidence: 99%
“…Uma série de estudos comparando esses dois tratamentos, com acompanhamento médio de 3,5 a 15 anos, demonstra que os resultados com a UNI foram significantemente melhores (34)(35)(36) . A HTO apresentou sucesso em 46%, 48% e 65% dos casos, enquanto que na UNI ocorreram 76%, 90% e 88% de bons resultados, respectivamente.…”
Section: Discussionunclassified